2022
DOI: 10.1264/jsme2.me21069
|View full text |Cite
|
Sign up to set email alerts
|

Antarctic Hairgrass Rhizosphere Microbiomes: Microscale Effects Shape Diversity, Structure, and Function

Abstract: The rhizosphere microbiome of the native Antarctic hairgrass Deschampsia antarctica from the central maritime Antarctic was investigated using 16S RNA metagenomics and compared to those of the second native Antarctic plant Colobanthus quitensis and closely related temperate D. cespitosa . The rhizosphere microbial communities of D. antarctica and D. cespitosa had high taxon richness, while that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 77 publications
1
4
0
Order By: Relevance
“…Yet, there are moss banks comparable in depth to those from Lazorev Bay within the more northern region of the Argentine Islands. The prevalence of micro-conditions over the latitude gradient is also shown by other studies(Nuzhyna et al 2021;Prekrasna et al 2022).Drainage is a crucial factor for the moss banks' development, as it was noted byOchyra et al (2008). Development of thick moss banks (1-2 m) on the well-drained substrate in the maritime Antarctic supports this statement.…”
supporting
confidence: 74%
“…Yet, there are moss banks comparable in depth to those from Lazorev Bay within the more northern region of the Argentine Islands. The prevalence of micro-conditions over the latitude gradient is also shown by other studies(Nuzhyna et al 2021;Prekrasna et al 2022).Drainage is a crucial factor for the moss banks' development, as it was noted byOchyra et al (2008). Development of thick moss banks (1-2 m) on the well-drained substrate in the maritime Antarctic supports this statement.…”
supporting
confidence: 74%
“…This sample exhibited the highest relative abundance of Actinobacteria among all samples in our study. Coupled with the elevated prevalence of Proteobacteria and Bacteroidetes, it mirrors a bacterial composition akin to previous Antarctic rhizoanalyses [61,62]. The high diversity could be attributed to the properties of the plant rhizosphere.…”
Section: Community Composition Of the Soil Sample Underneath A Patch ...mentioning
confidence: 61%
“…Studies in more temperate climate zones have shown decreased bacterial diversity in the plant rhizosphere than in the surrounding bulk soil due to selective interactions between the plant and the bacterial species [63]. However, Antarctic plants have also been shown to function as harbors against the unfavorable conditions of cold, oligotrophic deserts by moisture retention, easing temperature stress, preventing desiccation, and providing nutrients to the community [62].…”
Section: Community Composition Of the Soil Sample Underneath A Patch ...mentioning
confidence: 99%
“…This sample exhibited the highest relative abundance of Actinobacteria among all samples in our study. Coupled with the elevated prevalence of Proteobacteria and Bacteroidetes, it mirrors a bacterial composition akin to previous Antarctic rhizoanalyses [52,53]. The high diversity could be attributed to the properties of the plant rhizosphere.…”
Section: Community Composition Of the Soil Sample Underneath A Patch ...mentioning
confidence: 61%
“…Studies in more temperate climate zones have shown decreased bacterial diversity in the plant rhizosphere than in surrounding bulk soil due to selective interactions between the plant and the bacterial species [54]. However, Antarctic plants have also been shown to function as harbors against the unfavorable conditions of cold, oligotrophic deserts by moisture retention, easing temperature stress, preventing desiccation, and providing nutrients to the community [53].…”
Section: Community Composition Of the Soil Sample Underneath A Patch ...mentioning
confidence: 99%